Welcoming Syrian refugees to Canada technology-enabled social innovation - Cukier, Wendy; Jackson, Samantha (2017 IEEE Canada International Humanitarian Technology Conference (IHTC), 2017)
The Syrian refugee crisis has been termed “the greatest humanitarian crisis of the last century” and countries around the world have stepped up to provide safe haven to millions of Syrians fleeing violence. Canada's unique private sponsorship policy coupled with government sponsorship of refugees saw more than 40,000 welcomed to Canada in a matter of months prompting the need for new processes and solutions. Grassroots organizations emerged, with new partnerships, processes and approaches enabled with new applications of simple technologies and revealed opportunities to leverage and amplify government resources. While fragmented and sometimes primitive these efforts signaled new opportunities to create an innovative “sharing economy” approach. This paper will review the relations between these new initiatives, actors and networks and the opportunities to drive systems change through a social innovation lens.
Keywords: Canada; Réservé UdeM

Welcoming Syrian refugees to Canada technology-enabled social innovation - Cukier, Wendy; Jackson, Samantha (2017 IEEE Canada International Humanitarian Technology Conference (IHTC), 2017)
The Syrian refugee crisis has been termed “the greatest humanitarian crisis of the last century” and countries around the world have stepped up to provide safe haven to millions of Syrians fleeing violence. Canada's unique private sponsorship policy coupled with government sponsorship of refugees saw more than 40,000 welcomed to Canada in a matter of months prompting the need for new processes and solutions. Grassroots organizations emerged, with new partnerships, processes and approaches enabled with new applications of simple technologies and revealed opportunities to leverage and amplify government resources. While fragmented and sometimes primitive these efforts signaled new opportunities to create an innovative “sharing economy” approach. This paper will review the relations between these new initiatives, actors and networks and the opportunities to drive systems change through a social innovation lens.
Keywords: Canada; Réservé UdeM

Welcoming Syrian refugees to Canada technology-enabled social innovation - Cukier, Wendy; Jackson, Samantha (2017 IEEE Canada International Humanitarian Technology Conference (IHTC), 2017)
The Syrian refugee crisis has been termed “the greatest humanitarian crisis of the last century” and countries around the world have stepped up to provide safe haven to millions of Syrians fleeing violence. Canada's unique private sponsorship policy coupled with government sponsorship of refugees saw more than 40,000 welcomed to Canada in a matter of months prompting the need for new processes and solutions. Grassroots organizations emerged, with new partnerships, processes and approaches enabled with new applications of simple technologies and revealed opportunities to leverage and amplify government resources. While fragmented and sometimes primitive these efforts signaled new opportunities to create an innovative “sharing economy” approach. This paper will review the relations between these new initiatives, actors and networks and the opportunities to drive systems change through a social innovation lens.
Keywords: Canada; Réservé UdeM

Welcoming Syrian refugees to Canada technology-enabled social innovation - Cukier, Wendy; Jackson, Samantha (2017 IEEE Canada International Humanitarian Technology Conference (IHTC), 2017)
The Syrian refugee crisis has been termed “the greatest humanitarian crisis of the last century” and countries around the world have stepped up to provide safe haven to millions of Syrians fleeing violence. Canada's unique private sponsorship policy coupled with government sponsorship of refugees saw more than 40,000 welcomed to Canada in a matter of months prompting the need for new processes and solutions. Grassroots organizations emerged, with new partnerships, processes and approaches enabled with new applications of simple technologies and revealed opportunities to leverage and amplify government resources. While fragmented and sometimes primitive these efforts signaled new opportunities to create an innovative “sharing economy” approach. This paper will review the relations between these new initiatives, actors and networks and the opportunities to drive systems change through a social innovation lens.
Keywords: Canada; Réservé UdeM